Transformative driven mechanism framework as key success indicators for blended learning / Malissa Maria Mahmud - Mahmud, Malissa Maria (Institute of Graduate Studies, UiTM, 2017)
Current literature shows that blended learning has inevitably permeated and transformed the landscape of educational practices. However, in the same vein, it also depicts less consideration given to the impending gaps in the blended learning experience, consequently indicating a paucity of evidence in the context of these technological interventions. This study aimed to examine and identify the Key Success Indicators (KSIs) for blended learning approaches. The research is delineated in seven research questions postulated to address the overall facets in blended learning: the powerful and the combined Effect Sizes (ESs), the definitions of blended learning, the types of technological intervention, the specific ratio or percentage of intervention, and the quality of indicators determined in the language related blended learning studies and other subjects related to blended learning studies.